2017
DOI: 10.1016/j.physbeh.2016.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Sensory-specific satiety: Added insights from autonomic nervous system responses and facial expressions

Abstract: • We measured sensory-specific satiety with autonomic nervous system responses and facial expressions.• Consumption of the test meals resulted overall in increased heart rate, reduced skin conductance and skin temperature, as well as intensified disgusted facial expressions.• Skin conductance and skin temperature reflected effects of sensory-specific satiety.• Sad and angry facial expressions showed effects of sensory-specific satiety. a b s t r a c t a r t i c l e i n f o As a food is consumed, its perceived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 36 publications
3
16
0
Order By: Relevance
“…Our results agreed with those of He et al [30]. In this study, He and coworkers measured the changes of facial expression for the same, similar, and different taste conditions.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Our results agreed with those of He et al [30]. In this study, He and coworkers measured the changes of facial expression for the same, similar, and different taste conditions.…”
Section: Resultssupporting
confidence: 93%
“…Though it has been reported that the perception of basic tastes is linked with specific facial movements (for example, sourness with the lips or bitterness with the eyes and forehead) [29], many different variables can affect both FER and physiological changes: how hungry a consumer feels, the type of food tested, and the time elapsed since the beginning of the test. Even in tests as short as 10 s, a consumer may exhibit several facial expressions [30]. Moreover, changes in facial expression are harder to determine when tasting food products, compared to smelling a perfume or watching a video [25], since the jaw movement produced by chewing and the occasional facial occlusion (because of the hand that takes the sample to the mouth) are often the cause of misreading in FER algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, our present data suggest that the parasympathetic activity is not yet significantly altered because of any change in the sensitivity of the reflex bradycardia. Furthermore, it is well established in the literature that the increase in sympathetic activity induces an increase in plasma leptin (9) , dietary intakes (44,45) , adipose tissue (46,47) and IR (48,49) . In this way, in the present study, the increase in sympathetic activity must be involved in all cardio-metabolic alterations induced by the H diet of the progenitors that were transmitted to female and male F1H and F2H offspring.…”
Section: Discussionmentioning
confidence: 99%
“…Another study focusing on a temporal design revealed that repeated bites of the same food show an initial peak in happy emotions, with each successive bite showing a less intense response. The decrease is less if the next bite has a different flavor [52]. A temporal experimental design may be a more realistic model for evaluating beverages than a single consumption event and will certainly provide a broader set of data for analysis, yet literature is limited.…”
Section: Stimuli Presentationmentioning
confidence: 99%